A gut-derived Streptococcus salivarius produces the novel nisin variant designated nisin G and inhibits Fusobacterium nucleatum in a model of the human distal colon microbiome - Garreth W. Lawrence; Enriqueta Garcia-Gutierrez; A. Kate O’Mahony; Calum J. Walsh; Paula M. O'Connor; Máire Begley; Caitriona M. Guinane; Paul D. Cotter (mBio)
ABSTRACT Fusobacterium nucleatum is a human pathogen associated with intestinal conditions including colorectal cancer. Screening for gut-derived strains that exhibit anti-F. nucleatum activity in vitro revealed Streptococcus salivarius DPC6487 as a strain of interest. Whole-genome sequencing of S. salivarius DPC6487 identified a nisin operon with a novel structural variant designated nisin G. The structural nisin G peptide differs from the prototypical nisin A with respect to seven amino acids (Ile4Tyr, Ala15Val, Gly18Ala, Asn20His, Met21Leu, His27Asn, and His31Ile), including differences that have not previously been associated with a natural nisin variant. The nisin G gene cluster consists of nsgGEFABTCPRK with transposases encoded between the nisin G structural gene (nsgA) and nsgF, notably lacking an equivalent to the nisI immunity determinant. S. salivarius DPC6487 exhibited a narrower spectrum of activity in vitro compared to the nisin A-producing Lactococcus lactis NZ9700. Nisin G-producing S. salivarius DPC6487 demonstrated the ability to control F. nucleatum DSM15643 in an ex vivo model colonic environment while exerting minimal impact on the surrounding microbiota. The production of this bacteriocin by a gut-derived S. salivarius, its narrow-spectrum activity, and its anti-F. nucleatum activity in a model colonic environment indicates that this strain merits further attention with a view to harnessing its probiotic potential.IMPORTANCEFusobacterium nucleatum is a human pathogen associated with intestinal conditions, including colorectal cancer, making it a potentially important therapeutic target. Bacteriocin-producing probiotic bacteria demonstrate the potential to target disease-associated taxa in situ in the gut. A gut-derived strain Streptococcus salivarius DPC6487 was found to demonstrate anti-F. nucleatum activity, which was attributable to a gene encoding a novel nisin variant designated nisin G. Nisin G-producing S. salivarius DPC6487 demonstrated the ability to control an infection of F. nucleatum in a simulated model of the human distal colon while exerting minimal impact on the surrounding microbiota. Here, we describe this nisin variant produced by S. salivarius, a species that is frequently a focus for probiotic development. The production of nisin G by a gut-derived S. salivarius, its narrow-spectrum activity against F. nucleatum, and its anti-F. nucleatum activity in a model colonic environment warrants further research to determine its probiotic-related applications.